2013
DOI: 10.1002/ana.23876
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque hemorrhage on magnetic resonance imaging strongly predicts recurrent ischemia and stroke

Abstract: ObjectiveThere is a recognized need to improve selection of patients with carotid artery stenosis for carotid endarterectomy (CEA). We assessed the value of magnetic resonance imaging (MRI)-defined carotid plaque hemorrhage (MRIPH) to predict recurrent ipsilateral cerebral ischemic events, and stroke in symptomatic carotid stenosis.MethodsOne hundred seventy-nine symptomatic patients with ≥50% stenosis were prospectively recruited, underwent carotid MRI, and were clinically followed up until CEA, death, or isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 53 publications
4
122
0
Order By: Relevance
“…Moreover, although carotid atherosclerosis is a dynamic process, prospective evidence supports high-risk markers of plaque, such as intraplaque hemorrhage, as being relatively stable with time and conferring increased stroke risk for at least 5 years after their detection. 5 An additional recent study 27 also showed that high-risk elements such as intraplaque hemorrhage, fibrous cap abnormalities, and lipid cores were generally not significantly changed during a 1-year follow-up period. Therefore, although further investigation is needed, it is reasonable to hypothesize that our results could translate into a prospective CTA-based stroke prediction tool in carotid artery disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, although carotid atherosclerosis is a dynamic process, prospective evidence supports high-risk markers of plaque, such as intraplaque hemorrhage, as being relatively stable with time and conferring increased stroke risk for at least 5 years after their detection. 5 An additional recent study 27 also showed that high-risk elements such as intraplaque hemorrhage, fibrous cap abnormalities, and lipid cores were generally not significantly changed during a 1-year follow-up period. Therefore, although further investigation is needed, it is reasonable to hypothesize that our results could translate into a prospective CTA-based stroke prediction tool in carotid artery disease.…”
Section: Discussionmentioning
confidence: 97%
“…The 2 main pathophysiologic mechanisms underlying stroke risk in carotid artery disease are the propensity of plaque to locally embolize 4,5 and downstream hemodynamic compromise (low flow). 4,6,7 Although hypoperfusion and resultant slow flow from carotid disease likely play a role in a subset of strokes occurring in carotid stenosis, plaque instability causing distal embolus may be a relatively more influential etiologic factor for stroke in carotid disease in general.…”
mentioning
confidence: 99%
“…1,2 Recent literature confirms that plaque characteristics may contribute to specify subgroups with an increased risk of (recurrent) ischemic cerebral events. [3][4][5] Moreover, the presence of infarcts in the brain parenchyma that downstream to these lesions may be important for accurate risk stratification. Patients with infarcts and cerebral symptoms were found to profit more from carotid endarterectomy (CEA), compared with patients with just ocular symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] One such component of carotid plaque that has been identified as a component of advanced atherosclerotic lesions is intraplaque hemorrhage (IPH). When present in carotid atherosclerotic plaque, IPH has been associated with previous 7,8 and future 9 stroke and has been proposed as a possible marker of not only plaque inflammation 10 but also of generalized cardiovascular risk.…”
mentioning
confidence: 99%
“…4 However, a significant barrier to the widespread use of IPH assessment as a measure of embolic stroke risk has been that most studies have relied on high-resolution imaging by using specialized, dedicated MR imaging surface carotid coils 12 or black-blood coronal T1-weighted fat-suppressed MR imaging techniques. 9 Neither of these techniques are part of the standard sequences routinely obtained in MRA examinations, which rely on TOF techniques to assess luminal diameter stenosis. Recent reports have suggested that routinely performed MRA techniques used to measure stenosis, including 3D-TOF imaging, 13,14 can accurately predict IPH compared with histopathologic studies by the detection of intraplaque high-intensity signal (IHIS) relative to adjacent skeletal muscle.…”
mentioning
confidence: 99%